2014
DOI: 10.1158/1078-0432.ccr-14-1779
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis for the Association between Overall Survival and Progression-Free Survival in Gastrointestinal Stromal Tumor

Abstract: Purpose: Gastrointestinal stromal tumor (GIST) is a relatively rare tumor that is treated with targeted therapies in advanced stages. Randomized clinical trials (RCT) often require long followup and large sample sizes to evaluate overall survival (OS), the gold-standard measure of treatment efficacy. However, changes in therapy following disease progression may complicate survival assessments. Establishing surrogate endpoints may facilitate the drug approval and availability of new efficacious treatments; howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…In gastric cancer, Liu et al reported that PFS is strongly corrected with OS based on a NICE correlation model [26]. Özer-Stillman et al identified a strong relationship between median OS and PFS among gastrointestinal stromal tumor patients, especially in later lines of therapy based on meta-analysis [27]. However, others reached a different conclusion, questioning the validity of PFS as a surrogate endpoint for OS in gastric cancer patients [28, 29].…”
Section: Discussionmentioning
confidence: 99%
“…In gastric cancer, Liu et al reported that PFS is strongly corrected with OS based on a NICE correlation model [26]. Özer-Stillman et al identified a strong relationship between median OS and PFS among gastrointestinal stromal tumor patients, especially in later lines of therapy based on meta-analysis [27]. However, others reached a different conclusion, questioning the validity of PFS as a surrogate endpoint for OS in gastric cancer patients [28, 29].…”
Section: Discussionmentioning
confidence: 99%
“…Progression-free survival (PFS) and disease-free survival is suggested as an appropriate surrogate endpoint in phase II or III clinical trial conducted in solid tumour patients. The correlation between surrogate endpoints and OS has been validated in many types of cancer, including breast cancer, colorectal cancer, and lung cancer (Buyse et al , 2000b, 2007, 2009; Sargent et al , 2005; Petrelli and Barni, 2014; Blumenthal et al , 2015; Ozer-Stillman et al , 2015). However, there is no study that has evaluated the correlation between surrogate endpoints and OS in advanced HCC.…”
mentioning
confidence: 99%
“…However, in recent past (since 1990), a trend of decreased use of OS and increased use of event‐free survival/PFS as a primary endpoint has occurred in NHL . Furthermore, the surrogacy of PFS for OS has been established in various cancer settings such as colorectal cancer, gastrointestinal stromal tumors, metastatic prostate cancer, and hematological malignancies, including chronic lymphocytic leukemia, NHL, and MM . For instance, Lee et al found a good correlation ( R 2 = 0.90) between PFS and OS in aggressive NHL, although they could not establish the same correlation between PFS and OS in indolent NHL.…”
Section: Discussionmentioning
confidence: 99%